Los dispositivos de apoyo formal para personas mayores desde la perspectiva de sus familiares - Lombardo, Enrique (2023)
There is an increased demand for care systems for the elderly that had been attended to a few years ago by relatives, women in particular. This form of social device of care and support has entered a crisis. At present, various formal devices for care and attention to the needs of the elderly have been created, generating a gradual defamiliarization and growing articulation between formal and informal systems. The present work presents the testimony of relatives of elderly people who have found in these devices a resource that they value as a factor of shift in the elderly people´s life  and who, in the absence of such benefits, believe that their quality of life would deteriorate. a significant decline in their social life. The articulation between formal and informal supports promote a more active aging, physically, mentally and socially. The integration of the work of families with formal social support devices, whether in the public or private sphere, is a way to ensure compliance with human rights and the well-being of this population group